Renewable energy, circular economy indicators and environmental quality: A global evidence of 131 countries with heterogeneous income groups - Muhammad Tariq Majeed; Tania Luni (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2020)
Increasing global warming, degrading environmental quality, and waste ending in landfills have become threats to the sustainability of ecosystems. The circular economy (CE) offers an alternative approach to the linear economy, which lowers pressure on the ecosystem. Renewable energy, as an important pillar of CE, neither generates waste nor increases the extraction of limited resources. This study explores the dynamic links of renewable energy and CE with environmental quality. This study explains the important mechanisms of circular business models in the context of contingency theory, transaction cost theory, resource-based theory, networks-based theory, and agency theory. The empirical analysis is based on a global panel of 131 countries, including a disaggregated analysis for different groups of countries according to their income levels and European Union member countries. The 2nd generation tests namely "cross sectionally augmented IPS (CIPS), cross sectionally augmented Dickey Fuller test (CADF) and Westerlund cointegration test" are applied to test the relationships between the variables. We employ novel indicators of CE such as biowaste recycling, municipal waste recycling, e-waste recycling, packaging waste recycling, trade-in recyclables, and patents in recycling to examine their impacts on environmental quality. The results suggest that renewable energy and different measures of CE significantly improve environmental quality. Energy intensity, economic growth, and urbanization degrade the environment. The study suggests that CE measures need to be promoted to combat climate change.
Keywords: 330; biowaste recycling; CO2 emissions; municipal waste recycling; packagingwaste recycling; renewable energy consumption